L’agriculture en Famille : Travailler, Réinventer, Transmettre 2015
DOI: 10.1051/978-2-7598-1192-2.c008
|View full text |Cite
|
Sign up to set email alerts
|

Faire face à des questions de travail : les leviers mobilisés par des éleveurs laitiers

Abstract: Ce chapitre de l'ouvrage L'agriculture en famille : travailler, réinventer, transmettre est publié en Open Access sous licence creative commons CC-BY-NC-ND permettant l'utilisation non commerciale, la distribution, la reproduction du texte, sur n'importe quel support, à condition de citer la source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…For Central and Eastern Europe, Verhees et al [15] showed that land was the most important factor in developing a specific farming strategy. In France, Hostiou et al [26] observed that intensified farms with higher technology equipment sometimes employed more workers, and were the farms with significantly higher agricultural area, percentage of corn silage, number of cows and milk quota. In the Netherlands, Samson et al [36] showed that production intensity, number of cows, modernity of technology and availability of land were important factors in DP increase strategies.…”
Section: Plos Onementioning
confidence: 99%
“…For Central and Eastern Europe, Verhees et al [15] showed that land was the most important factor in developing a specific farming strategy. In France, Hostiou et al [26] observed that intensified farms with higher technology equipment sometimes employed more workers, and were the farms with significantly higher agricultural area, percentage of corn silage, number of cows and milk quota. In the Netherlands, Samson et al [36] showed that production intensity, number of cows, modernity of technology and availability of land were important factors in DP increase strategies.…”
Section: Plos Onementioning
confidence: 99%
“…Des études françaises soulignent également l'importance du temps d'astreinte (deux fois le temps de travail), qui pèserait surtout sur les éleveurs travaillant seuls. Le temps de travail varie cependant beaucoup selon l'orientation de l'élevage, ses équipements, la main-d'oeuvre, la localisation de l'exploitation et la rationalité privilégiée par l'éleveur (Hostiou et al, 2014). Que les systèmes soient mixtes ou spécialisés ne différencie pas le temps de travail.…”
Section: ❚ ❚ Une Compétitivité « Hors Coûts » Valorisant La Qualité Eunclassified
“…For Central and Eastern Europe, Verhees et al (2018) [13] showed that land was the most important factor in developing a specific farming strategy. In France, Hostiou et al (2015) [21] observed that intensified farms with higher technology equipment sometimes employed more workers, and were the farms with significantly higher agricultural area, percentage of corn silage, number of cows and milk quota. In the Netherlands, Samson et al (2016) [14] showed that production intensity, number of cows, modernity of technology and availability of land were important factors in DP increase strategies.…”
Section: Production Factorsmentioning
confidence: 99%